2021
DOI: 10.3892/or.2021.8167
|View full text |Cite|
|
Sign up to set email alerts
|

Plasma‑derived exosomal pyruvate kinase isoenzyme type M2 accelerates the proliferation and motility of oesophageal squamous cell carcinoma cells

Abstract: Exosomal pyruvate kinase isoenzyme type M2 (PKM2) has been found to play a key role in the progression of human hepatocarcinoma. However, exosomal PKM2 (especially plasma-derived exosomal PKM2), in patients with oesophageal squamous cell carcinoma (ESCC) has not been well defined. In the present study, plasma-derived exosomes were isolated from healthy controls and patients with ESCC, and identified by transmission electronic microscopy, western blotting, nano-flow cytometry, nanoparticle tracking and phagocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The metabolic switch of liver nonparenchymal cells has been shown to be mediated by exosomal PKM2 in activated hepatic stellate cells [ 34 ]. Additionally, it was demonstrated that exosomal PKM2 transmitted in plasma reinforced growth and motility in esophageal squamous cell carcinoma cells [ 35 ]. In prostate carcinoma, bone metastases were found to be motivated by exosomal PKM2 transmission into bone stroma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic switch of liver nonparenchymal cells has been shown to be mediated by exosomal PKM2 in activated hepatic stellate cells [ 34 ]. Additionally, it was demonstrated that exosomal PKM2 transmitted in plasma reinforced growth and motility in esophageal squamous cell carcinoma cells [ 35 ]. In prostate carcinoma, bone metastases were found to be motivated by exosomal PKM2 transmission into bone stroma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they are rarely present in blood circulation until tumor sizes increase to some degree; therefore, it is difficult to use these molecules for early diagnosis [ 132 , 134 , 135 ]. In fact, various studies indicate an association between EVs and diagnostic potential or prognosis prediction, so nucleic acids in EVs or membrane proteins on the surface of EVs might be novel biomarkers [ 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 ]. In this review, we have summarized that EVs mediate the immune evasion of tumors and induce tumor metastasis; below, we will show that EVs might be a diagnostic biomarker of tumor metastasis or an indicator of the immune response to tumors.…”
Section: Clinical Application Of Evsmentioning
confidence: 99%
“…1C), 104,125 which is linked with the production of EVs that contain increased levels of GAPDH, [126][127][128] and enolase. [129][130][131] Herein, we will discuss the current efforts in applying dynamic 3D culture for large scale EV production.…”
Section: Dynamic 3d Cultures In Large Scale Ev Productionmentioning
confidence: 99%